FORMATION OF LEXICAL SKILLS THROUGH PHRASEOLOGY IN KARAKALPAK AND ENGLISH LANGUAGES (International journal of artificial intelligence, 2025)
Phraseology has an incomparable contribution to the formation language as an integral part of any language and its own treasure. This article covers issues such as the formation of lexical skills through phraseology in English and further enhancing the means, affectivity of the sentence.